Identifying Urban Heritage Facility Management Support Services Considering World Heritage Sites - Bintang Noor Prabowo; Alenka Temeljotov Salaj; Jardar Lohne (Urban Science, 2023)
Whether public sectors or private institutions, in-house or outsourced, building-level or urban-scale, the critical role of facility management (FM) is to support the core business activities of an organization in accomplishing its objectives. Through the services it manages and provides, FM impacts people’s health, well-being, and quality of life. While there is no difficulty in defining a corporation, organization, or institution’s core business, defining the core business of a city as an institution is not widely discussed in the urban-scale facility management literature. By using a narrative research approach from the available literature, this study seeks to shed light on potential justifications for a city’s “core business” and its possible support services. The context of the World Heritage site is used to provide a sharper perspective on the possible urban-scale support services customized for urban heritage areas. This study suggests that a city’s primary objective is to maintain and possibly attract new “desirable” citizens through the provision of excellent services, a quality-built environment, a sense of well-being, health, safety and security, and economic growth. Consequently, the integration of urban-scale support services must be aligned with the purpose of the city, or the World Heritage site, to be specific.